Good night the pleasure was ours - Grubbs, David, 1967- (Book collections on Project MUSE., 2022)
"Good night the pleasure was ours is the third and final entry in an ensemble of book-length poems that includes Now that the audience is assembled and The Voice in the Headphones. Whereas the other two books focus on the concert and the recording studio, Good night the pleasure was ours describes three decades worth of touring, going back as far as David Grubbs' high school band Squirrel Bait. These groundbreaking works, which can be read in any sequence, spring from the idea of literature as a medium for writing about music. This trilogy represents through close description three sites of musical experience: the concert, the recording studio, and the tour. They aim to open up music writing to greater experimentation while at the same time serving a documentary function amidst changing musical cultures"--